Measuring Digital Inclusiveness and Its Impact on Gender Inequality for Women - Amelia, Dhea Rizky; Khoiry, I'tishom Al; Aini, Nurul; Praatmana, Nanang Dwi; Hadi, Caraka (EconBank: Journal of Economics and Banking, 2025)
This study investigates whether digitalization reduces or reinforces the gender gap in working hours in Indonesia. Using the 2023 National Labor Force Survey (SAKERNAS) and the Oaxaca–Blinder decomposition approach, it compares the working hour disparities between men and women in both digital and non-digital employment. The findings reveal that the gender gap in working hours is relatively smaller in the digital sector and is largely explained by observable characteristics such as education, formal employment, and training. In contrast, a significant portion of the gap in the non-digital sector remains unexplained, indicating strong influences of social norms and structural biases. These results suggest that digitalization can enhance women's labor market inclusion if supported by affirmative policies that improve access to technology and training. Meanwhile, the non-digital sector still requires broader structural reforms to achieve gender equality in working hours.